2022
DOI: 10.1101/2022.03.15.484419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A subpopulation of Talin 1 resides in the nucleus and regulates gene expression

Abstract: Talin 1 (TLN1) is best known for its role at focal adhesions, where it activates β-integrin receptors and transmits mechanical stimuli to the actin cytoskeleton. Interestingly, the localization of TLN1 is not restricted to the focal adhesions, but its function in other cellular compartments remains poorly understood. By utilizing both biochemical and confocal microscopy analyses, we show that TLN1 localizes to the nucleus and that it strongly interacts with the chromatin. Importantly, depletion of endogenous T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…In cancer cells, on the other hand, the mechanism is not properly regulated and FAK is overexpressed [ 39 41 ]. Control melanoma cells have significant focal points and vinculin around the nucleus, the latter likely resulting from interactions with talin localized in the cell nucleus [ 42 , 43 ]. In treated melanoma cells, we found vinculin to be delocalized over the entire cytoplasmic fluid, consistent with an increase in its inactive form, which is consistent with the activation of FAK regulation mechanisms [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, on the other hand, the mechanism is not properly regulated and FAK is overexpressed [ 39 41 ]. Control melanoma cells have significant focal points and vinculin around the nucleus, the latter likely resulting from interactions with talin localized in the cell nucleus [ 42 , 43 ]. In treated melanoma cells, we found vinculin to be delocalized over the entire cytoplasmic fluid, consistent with an increase in its inactive form, which is consistent with the activation of FAK regulation mechanisms [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Talin contains an N-terminal FERM domain that binds and regulates the conformation of the integrin receptor and induces intracellular force sensing, and a C-terminal F-actin–binding domain ( Fig 2 ). In human epithelial cells, talin-1 was found recently in the nucleus, where it interacts with the chromatin and localizes primarily to the nucleolus ( Da Silva et al, 2022 Preprint ). In Drosophila , the talin homologue (rhea) regulates DE-cadherin at the transcriptional level; however, at present, it seems more likely that talin acts in the cytoplasm to control the activity of a transcriptional factor rather than being directly involved in gene expression in the nucleus ( Bécam et al, 2005 ).…”
Section: The Ferm Domain and Its Historymentioning
confidence: 99%
“…Talin-1 is another important adaptor protein, mediating both mechanical dependent signaling and binding to the Actin cytoskeleton. Recently, Talin - 1 was shown to localize to the nucleus, bind chromatin, and when nuclear localization was enhanced with addition of a genetic nuclear localization signal, gene expression changes were observed ( Da Silva et al, 2022 ).…”
Section: Cell Adhesion Proteins As Gene Regulatorsmentioning
confidence: 99%
“…The nuclear function of three of the focal adhesion proteins, Talin-1, FAK, and Zyxin have been explored to some detail. For instance, a recent paper demonstrated that Talin-1 depletion altered gene expression and was copurified with the chromatin fraction of cells ( Da Silva et al, 2022 ), but the direct result of this interaction is yet forthcoming. Importantly, the relevance of this nuclear localization of Talin-1 in both development and disease remains a key question.…”
Section: Nuclear Function Of Cell Adhesion Proteins and Misregulation...mentioning
confidence: 99%